2022
DOI: 10.1177/11206721221095598
|View full text |Cite
|
Sign up to set email alerts
|

Descemet stripping only and ripasudil for the treatment of traumatic Descemet’s membrane ruptures

Abstract: Purpose Descemet´s membrane ruptures (with a discontinuation of Descemet´s membrane and double detached coiled edges) in the context of complicated anterior segment surgery have rarely been described and its management can be challenging. We report a modified Descemet stripping only (DSO) technique associated with ripasudil drops to treat these cases when other techniques fail. Methods We describe two cases of large Descemet´s membrane detachments associated with Descemet´s ruptures after cataract surgery that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Cataract or anterior segment surgeries are known to be associated with a risk of postoperative corneal oedema due to endothelial cell damage. Studies have shown that administering ripasudil in the post-operative period has a protective effect on endothelial cell density [38], and may improve visual recovery after complicated procedures [39,40]. In both Descemet's Stripping Automated Endothelial Keratoplasty (DSAEK) and penetrating keratoplasty corneal grafts that failed to clear with conservative management, vision can be rescued with ripasudil therapy [41].…”
Section: Ripasudil In Corneal Diseasesmentioning
confidence: 99%
“…Cataract or anterior segment surgeries are known to be associated with a risk of postoperative corneal oedema due to endothelial cell damage. Studies have shown that administering ripasudil in the post-operative period has a protective effect on endothelial cell density [38], and may improve visual recovery after complicated procedures [39,40]. In both Descemet's Stripping Automated Endothelial Keratoplasty (DSAEK) and penetrating keratoplasty corneal grafts that failed to clear with conservative management, vision can be rescued with ripasudil therapy [41].…”
Section: Ripasudil In Corneal Diseasesmentioning
confidence: 99%
“…DSO combined with postoperative topical ROCKi (ripasudil) has also been reported to be effective in managing DM rupture [30 ▪ ]. Fernandez Lopez et al [30 ▪ ] described two cases where a modified DSO was performed in combination with postoperative ripasudil to treat corneal oedema following iatrogenic DM rupture occurring during cataract surgery.…”
Section: Expanding Roles For Descemet's Stripping Onlymentioning
confidence: 99%
“…DSO combined with postoperative topical ROCKi (ripasudil) has also been reported to be effective in managing DM rupture [30 ▪ ]. Fernandez Lopez et al [30 ▪ ] described two cases where a modified DSO was performed in combination with postoperative ripasudil to treat corneal oedema following iatrogenic DM rupture occurring during cataract surgery. In both cases corneal clarity was not achieved until the ruptured DM was removed during the subsequent DSO, possibly due to the scrolled DM acting as a barrier to cell migration.…”
Section: Expanding Roles For Descemet's Stripping Onlymentioning
confidence: 99%